Contribution to study of the superfamily Cleroidea (Coleoptera) from Iran and adjacent countries: a checklist of Melyridae, Prionoceridae and Trogossitidae - Mirutenko, Vladyslav; Ghahari, Hassan (Zootaxa, 2018)
The fauna of Iranian Melyridae, Prionoceridae and Trogossitidae (Coleoptera: Cleroidea) is discussed in this paper. In total 13 species of Melyridae from 3 genera Anthodromius Redtenbacher, Cerallus Jacquelin du Val and Melyris Fabricius, one species of Prionoceridae and one species of Trogossitidae are listed as the fauna of Iran. Cerallus pilosus Reitter, 1889 (Melyridae) and Nemozoma elongatum Linnaeus, 1761 (Trogossitidae) are new records for the fauna of Iran.